Susceptibility of Pepper weevil (Anthonomus eugenii Cano) (Coleoptera: Curculionidae) to seven insecticides in rural areas of Baja California Sur, México. - Servin-Villegas, Rosalía; García-Hernández, José L.; Tejas-Romero, Armando; Martínez-Carrillo, José L.; Toapanta, M. A. (Instituto de Ecología, A.C., 2008)
The susceptibility of the pepper weevil (Anthonomus eugenii), collected from Baja California Sur, Mexico, to seven insecticides was determined. Acontact, residual exposition method was used to obtain the lethal concentrations fifty (LC50) and the diagnostic concentration (LC95) of organophosphates (OF), carbamates (CA), pyrethroids (PIR), and organochlorine (OC) insecticides used to control pepper weevils from two agricultural areas (Los Planes and Todos Santos) in Southern Baja California Peninsula, as well as on a pepper weevil population not exposed to insecticides (PWIF) for two years. The highest LC50’s were obtained for methomyl (CA) and oxamyl (CA), followed by methamidophos (OF), endosulfan (OC), cyfluthrin (PIR) and azinphos-methyl (OF). The lowest LC50’s were observed for carbaryl (CA). The field population from Todos Santos showed lower susceptibility than the population from Los Planes to insecticides as methomyl, oxamyl, and carbaryl, while with methamidophos, azinphos-methyl, and cyfluthrin, the LC50 showed higher values. The PWIF population presented the lowest LC50 values of all three populations tested. However, in most cases, the difference was not significant in relation to the two field populations, thus the PWIF population needs to be kept free of insecticides for longer periods to establish a susceptibility baseline for Anthonomus eugenii.